2016
DOI: 10.1039/c6cp01151a
|View full text |Cite
|
Sign up to set email alerts
|

Methanol diffusion in zeolite HY: a combined quasielastic neutron scattering and molecular dynamics simulation study

Abstract: The diffusion of methanol in zeolite HY is studied using tandem quasielastic neutron scattering (QENS) experiments and molecular dynamics (MD) simulations at 300-400 K. The experimental diffusion coefficients were measured in the range 2-5 × 10(-10) m(2) s(-1) and simulated diffusion coefficients calculated in the range of 1.6-3.2 × 10(-9) m(2) s(-1). Activation energies were measured as 8.8 and 6.9 kJ mol(-1) using QENS and MD respectively. Differences may be attributed predominantly to the experimental use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 82 publications
6
34
0
Order By: Relevance
“…The significant broadening in HY is completely consistent with diffusing methanol. MD simulations 29 supported this interpretation and showed the presence of hydrogen-bonded methanol in the pores. In contrast, the close fit to the resolution function in H-ZSM-5 suggests that methanol is immobile on the instrumental time scale.…”
Section: Qens and Ins Studies Of The Methanol-to-hydrocarbon (Mth) Prsupporting
confidence: 63%
See 1 more Smart Citation
“…The significant broadening in HY is completely consistent with diffusing methanol. MD simulations 29 supported this interpretation and showed the presence of hydrogen-bonded methanol in the pores. In contrast, the close fit to the resolution function in H-ZSM-5 suggests that methanol is immobile on the instrumental time scale.…”
Section: Qens and Ins Studies Of The Methanol-to-hydrocarbon (Mth) Prsupporting
confidence: 63%
“…This combination of techniques has proved to give unique insight into molecular behaviour in catalytic systems 15,[25][26][27][28][29] and will feature prominently in this article.…”
Section: Neutron Spin-echo Techniquesmentioning
confidence: 99%
“…We observed that 1 ns was enough to obtain mean-squared displacement (MSD) plots with acceptable linearity to calculate the self-diffusivity of phenol throughout the pore system of zeolite Beta. 38,39 The MSD was calculated from the variation in the coordinates of the centre of mass of the molecules. The selfdiffusion coefficients were derived from the Einstein relationship:…”
Section: Zeolitementioning
confidence: 99%
“…The dynamical characteristics derived from the MD analysis are an essential complement to the QENS experiments, as shown in previous reports on a range of zeolite-sorbate systems. [35][36][37][38][39] QENS observables such as the intermediate scattering function and its temporal Fourier transform, the dynamic structure factor, may be calculated directly to compare simulation results with experiment. 40,41 In the present work, we have studied the mobility of phenol in zeolite Beta using QENS experiments complemented by density functional theory (DFT) calculations and classical MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interactions between CO 2 molecules, it does not behave like ideal gas. Catlow et al studied methanol diffusion in zeolite HY with quasi‐elastic neutron scattering, which can hardly be done by other methods due to the reactivity of methanol and crystal size …”
Section: Traditional Methods Of Studying Diffusion and Deactivation Imentioning
confidence: 99%